La formación integral del estudiante y la formación continua de los profesores en la Educación Superior cubana: el papel de la Responsabilidad Social Universitaria (RSU) en su consecución - Victoria Ojalvo Mitrany; Laura Curiel Peón (LED Edizioni Universitarie, 2015)
The present article analyzes the main demands facing teachers and students at the present time in the context of higher education in Cuba. These two actors in the educational process should take up their activities with a high sense of responsibility and social commitment to the implications in the social and economic changes that are being developed in the country. Improved training of students and teachers is being investigated worldwide: currently studying University Social Responsibility (URS) are proving their worth in the achievement of such important purposes. In this sense, the Group of Social Interaction University, the Centre of Studies for the Improvement of Higher Education, University of Havana is developing research about training with URS students and professors as a contribution to achieve an ideal model of body students and professorate. This training process is designed to promote the social, ethical and emotional for the personal and social welfare.